Interaction of humic acids with soil minerals. Adsorption and surface aggregation induced by Ca2+ - Kloster, Nanci Soledad (2015)
Humic acids (HA) interact with the surface of mineral particles leading to the formation of clay-humic complexes that affect the transport of nutrients and contaminants in the environment, soil structure, soil erosion and carbon sequestration by soils. The interaction is influenced by the presence of multivalent ions, such as Ca2+, which enhances the uptake of HA by the particles. This article reports the effects of Ca2+ on the interaction between a HA and a soil clay fraction, both obtained from the same soil sample. The study was performed by using zeta potential measurements, HA adsorption isotherms, Ca2+ adsorption isotherms and microscopy. The results show that at low HA concentrations and low Ca2+ concentrations HA adsorption takes place, but that at high concentrations surface aggregation/precipitation also takes place, process that was seldom reported or analysed in the literature. HA adsorption isotherms only give the overall HA uptake by the solid but they do not allow to differentiate HA adsorption from surface aggregation. However, HA adsorption vs. Ca2+ concentration plots and Ca2+ adsorption isotherms at different HA concentrations can distinguish these two processes quite clearly. In addition, surface aggregation could be undoubtedly observed with optical microscopy. Surface aggregation starts to take place at a 0.7 mM Ca2+ concentration, which is lower than the Ca2+ concentration needed to start HA aggregation in solution. This indicates that the surface of soil minerals acts as a nucleation centre for HA aggregation.